Family and polygenic hypercholesterolemia: similarities and differencies by long-term follow-up - B M Lipovetskiy; B M Lipovetsky (Терапевтический архив, 2009)
Aim. Detection and analysis of similarities and differences in patients with family and polygenic hypercholesterolemia (FHCE and PHCE). Material and methods. The study included 100 patients with FHCE and 80 PHCE patients with LDLP cholesterol level at least 4.3 mmol/l (170 mg/dl). Results. The patients differed by age, gender, severity of hypercholesterolemia, clinical symptoms. Half of PHCE patients had myocardial infarction, 18% had angina pectoris, 29% cerebrovascular events. The disease was asymptomatic in 19% FHCE patients, 33% had myocardial infarction, 15% - angina pectoris, 12% - cerebrovascular events, 9% - aortic problems. Total mortality in both groups was similar - 32 and 33%. Long-term treatment with statins reduced lethality twice both in FHCE and PHCE. Adequate statin therapy prolonged life of the patients by 11 years, on the average. Conclusion. Regular treatment of patients with hypercholesterolemia reduces lethality and prolong their life span.